ЛИЧНОСТНЫЕ ОСОБЕННОСТИ ПЕДАГОГОВ КАК ДЕСКРИПТОРЫ ПРОЯВЛЕНИЯ ПСИХОЛОГИЧЕСКИХ БАРЬЕРОВ В ИННОВАЦИОННОМ ПРОЦЕССЕ - Ладзина Н.А.¹ , Акажанова А. Т.2 , Бисенова Ш.3, Н.А. А. Т. Ш.3 (Вестник КазНПУ имени Абая. Серия: Психология, 2021)
This article presents a study of the relationship of personal characteristics and the manifestation of this fact in the innovation process. The indicated problem appears in psychology as a manifestation of conservatism, conformism, and other psychological and socio-psychological phenomena, collectively called “psychological barriers”, which are understood as difficulties in a person’s activity, caused by the characteristics of his mental state and personal characteristics “preserving” the potential of his activity. types of psychological barriers, their specificity in the innovation process is disclosed. The article shows that such personality characteristics as the external locus of control, external professional motivation, conservatism and certain value orientations influence the rejection of innovations and will be more pronounced among high school teachers than among higher school teachers. The results and conclusions presented by the authors can be useful in the preparatory stage of innovations in the education system to prevent the formation of psychological barriers and increase the effectiveness of the implementation process